A Case Report of Acute-on-Chronic Methemoglobinemia - Gabriel Lathrop; Rodney Fullmer (Clinical Practice and Cases in Emergency Medicine)
Introduction: Methemoglobinemia is a rare hematologic disorder of hemoglobin, in which iron contained within the heme moiety becomes oxidized from ferrous iron to ferric iron at a concentration greater than 1% in the blood. This biochemical change reduces binding affinity for oxygen, leading to impaired oxygen deposition in tissues and subsequent hypoxia and hypoxemia. The etiology of methemoglobinemia is often acquired from exposure to oxidizing agents, commonly antibiotics such as dapsone or local anesthetics such as benzocaine. A rare cause results from congenital deficiency of cytochrome b5 reductase, a nicotinamide adenine dinucleotide dependent enzyme within red blood cells that donates electrons to reduce ferric to ferrous iron. Case Report: A 22-year-old previously healthy female was referred to the emergency department (ED) by her dentist one week after a dental procedure where she was noted to have low oxygen saturation and dark blood upon reported exposure to benzocaine. Upon arrival to the ED one week after exposure, her vitals were notable for oxygen saturation of 89% on room air. She was placed on 6 liters supplemental nasal cannula oxygen with subsequent improvement of oxygen saturation to 92%. Her exam was concerning with pale appearance, perioral cyanosis, and dusky fingertips. Her laboratory studies were most notable for serum methemoglobin level critically elevated to 31.6% one week after exposure, and she received 1 milligram per kilogram methylene blue in the ED with subsequent reduction of methemoglobin to 0.7%. The patient’s inpatient workup revealed a congenital deficiency in cytochrome b5 reductase. Conclusion: Methemoglobinemia arises when there is a mismatch between the formation of oxidized ferric iron and the subsequent reduction to ferrous iron. Classically, methemoglobinemia is an acquired pathologic process from acute exposure to any number of oxidative stressors; in rare cases, methemoglobinemia is caused by congenital deficiency in red blood cell-reducing enzymes. We report a case of an acquired methemoglobinemia with prolonged methemoglobinemia in a patient with undiagnosed congenital methemoglobinemia from cytochrome b5 reductase deficiency.